Inverse scattering problem with Levinson formula for eigenparameter‐dependent discrete Sturm–Liouville equation - Koprubasi, Turhan; Mohapatra, Ram N. (Wiley, 2022)
In this paper, an inverse scattering problem for discrete Sturm–Liouville equation with eigenparameter‐dependent boundary condition is investigated. In quest of finding scattering function and the main equation of this problem, the uniqueness of the kernel is proven. Also, an appropriate Levinson‐type formula based on the continuity of scattering function is given.
Keywords: Sturm-Liouville theory; scattering function; Scattering theory, inverse scattering involving ordinary differential operators; Boundary value problems for difference equations; eigenparameter; Discrete version of topics in analysis; Difference operators; discrete equation; Levinson formula; Sturm-Liouville problem